Characterization of activated carbon produced from urban organic waste - Abdul Gani Haji; Gustan Pari; Muhammad Nazar; H Habibati (International Journal of Science and Engineering, 2013)
The difficulties to decompose organic waste can be handled naturally by pyrolisis so it can  decomposes quickly that produces charcoal as the product. This study aims to investigate the characteristics of activated carbon from urban organic waste. Charcoal results of pyrolysis of organic waste activated with KOH 1.0 M at a temperature of 700 and 800oC for 60 to 120 minutes. Characteristics of activated carbon were identified by Furrier Transform Infra Red (FTIR), Scanning Electron Microscopy (SEM), and X-Ray Diffraction (XRD). However, their quality is determined yield, moisture content, ash, fly substances, fixed carbon, and the power of adsorption of iodine and benzene. The identified functional groups on activated carbon, such as OH (3448,5-3436,9 cm-1), and C=O (1639,4 cm-1). In general, the degree and distance between the layers of active carbon crystallites produced activation in all treatments showed no significant difference. The pattern of activated carbon surface topography structure shows that the greater the pore formation in accordance with the temperature increase the more activation time needed. The yield of activated carbon obtained ranged from 72.04 to 82.75%. The results of characterization properties of activated carbon was obtained from 1.11 to 5.41% water, 13.68 to 17.27% substance fly, 20.36 to 26.59% ash, and 56.14 to 62.31% of fixed carbon . Absorption of activated carbon was good enough at 800oC and 120 minutes of activation time, that was equal to 409.52 mg/g of iodine and 14.03% of benzene. Activated carbon produced has less good quality, because only the water content and flying substances that meet the standards.Doi: 10.12777/ijse.5.2.89-94 [How to cite this article: Haji, A.G., Pari, G., Nazar, M., and Habibati.  (2013). Characterization of activated carbon produced from urban organic waste . International Journal of Science and Engineering, 5(2),89-94. Doi: 10.12777/ijse.5.2.89-94]